Application of Eudragit RS 30D as a Potential Drug Release Retardant of Acetaminophen and Caffeine for Prolonged Duration of Comfort - Lailoona Jaweed; Huma Dilshad; Ghulam Sarwar (International Journal of Polymer Science)
The objective of the study is to formulate an extended release matrix tablet dosage form containing acetaminophen and caffeine by applying polymer technology which will relieve all kinds of pain for about 12 hours. Considering the fact that there is no such formulation available in the pharmaceutical market, it is expected that this drug could be an effective introduction. Hydrophobic polymers have a great application in pharmaceutical sciences as they retard the release of water-soluble drugs and give prolonged effect. Eudragit RS 30D was used to prepare 3 formulations (EF1, EF2, and EF3) containing varying concentrations of polymer, through the wet granulation method. Each tablet contained 1000 mg of acetaminophen and 130 mg of caffeine including other suitable excipients. All pharmacopeial and nonpharmacopeial tests were conducted to determine the quality of dosage form and to identify optimized formulation among EF1-EF3. Dissolution was conducted on similar gastric conditions through which different kinetic models were applied using DDSolver. For 12 hrs of dissolution, caffeine was released from EF1, EF2, and EF3 with the percentage release in the range from 99.85% to 100.65%, 99.32% to 100.28%, and 98.09% to 100.77%, respectively. For acetaminophen, the percent release was from 99.81% to 100.91%, 100.24% to 100.91%, and 86.81% to 95.73% for EF1-EF3, respectively. Results concluded that EF2 is the most optimized drug having all physicochemical quality control tests within the specified limits. On applying different models like zero-order, Hixson-Crowell, Higuchi, and Korsmeyer-Peppas upon use, it is concluded that the formulation follows Korsmeyer-Peppas as it was the best-fitted model with the r2 value closest to 0.999. EF2 is considered as a potential drug to be manufactured that will give prolonged relief against pain and will decrease compliance issues related to dosing frequency.